Some like it hot: Temperature and pH modulate larval development and settlement of the sea urchin Arbacia lixula - Wangensteen, Owen S.; Dupont, Sam; Casties, Isabel; Turon, Xavier; Palacín, Cruz (Journal of Experimental Marine Biology and Ecology, 2013)
8 páginas, 7 figuras, 5 tablas. We studied the effects of temperature and pH on larval development, settlement and juvenile survival of a Mediterranean population of the sea urchin Arbacia lixula. Three temperatures (16, 17.5 and 19 °C) were tested at present pH conditions (pHT 8.1). At 19 °C, two pH levels were compared to reflect present average (pHT 8.1) and near-future average conditions (pHT 7.7, expected by 2100). Larvae were reared for 52-days to achieve the full larval development and complete the metamorphosis to the settler stage. We analyzed larval survival, growth, morphology and settlement success. We also tested the carry-over effect of acidification on juvenile survival after 3 days. Our results showed that larval survival and size significantly increased with temperature. Acidification resulted in higher survival rates and developmental delay. Larval morphology was significantly altered by low temperatures, which led to narrower larvae with relatively shorter skeletal rods, but larval morphology was only marginally affected by acidification. No carry-over effects between larvae and juveniles were detected in early settler survival, though settlers from larvae reared at pH 7.7 were significantly smaller than their counterparts developed at pH 8.1. These results suggest an overall positive effect of environmental parameters related to global change on the reproduction of A. lixula, and reinforce the concerns about the increasing negative impact on shallow Mediterranean ecosystems of this post-glacial colonizer. This work was funded by projects CTM2010- 22218 from the Spanish Government, BIOCON 08-187/09 from BBVA Foundation, EPOCA (European Project on Ocean Acidification) N211384 from the European Community's Seventh Framework Programme (FP7/2007-2013) and grants from ASSEMBLE (Association of European Marine Biology Laboratories) and KVA (The Royal Swedish Academy of Sciences). OSW was funded by a grant from AGAUR BE-DGR 2012 (Generalitat de Catalunya). SD is funded by the CeMEB and supported ...